RAINFALL EROSIVITY IN MUNICIPALITIES OF THE BRAZILIAN CERRADO BIOME (Nativa, 2022)
ABSTRACT: The objective of this work was to estimate the rainfall erosivity in 101 municipalities in the Brazilian Cerrado biome. First, a filling of missing data was carried out for 81 rain gauge stations, with a 20-year historical series, in the states of Mato Grosso (MT), Mato Grosso do Sul (MS), Minas Gerais (MG), and Goiás (GO). The corrected data were subjected to 16 regionally calibrated equations, which enabled the determination of the rainfall erosivity. The results indicated that municipalities in northeastern MS present the highest monthly erosivity indexes (El30m), reaching 2,796.5 MJ mm ha-1 h-1 year-1 in January, whereas the lowest index for this same month was 733.0 MJ mm ha-1 h-1 in the eastern MT. The rainfall annual erosivity, or R factor, varied between 3,713.1 and 12,345.6 MJ mm ha-1 h-1 year-1, with the lowest values for municipalities in eastern MT and the highest values for those in northeastern MS. Although the municipalities studied are within the same biome, the spatial distribution makes them present regional effects due to different climatic factors, resulting in different rainfall volumes and intensities, which is reflected in the results of the monthly erosivity index and R factor.Keywords: rainfall stations; R fator; fill missing data; precipitation. Erosividade da chuva em municípios do Cerrado brasileiro  RESUMO: O objetivo deste trabalho é estimar a erosividade da chuva em 101 municípios localizados no bioma Cerrado. Para tanto, inicialmente foi realizado o preenchimento de falhas para 81 estações pluviométricas, com série histórica de 20 anos, localizadas nos estados de Mato Grosso, Mato Grosso do Sul, Minas Gerais e Goiás, posteriormente com os dados consistidos, foram aplicadas 16 equações calibradas regionalmente, permitindo determinada a erosividade da chuva. Os resultados apontaram que os municípios localizados na região Nordeste de MS, apresentam os maiores índices El30m, chegando a 2.796,5 MJ mm ha-1 h-1 ano-1 no mês de janeiro, enquanto para o mesmo mês, o menor índice foi de 733,0 MJ mm ha-1 h-1  no Leste de MT. A erosividade da chuva anual ou fator R variou entre 3.713,1 a 12.345,6 MJ mm ha-1 h-1 ano-1, com os menores valores para os municípios da região Leste de MT e o maiores para a região Nordeste de MS. Apesar dos municípios estudados estarem localizados dentro do mesmo bioma, a distribuição espacial lhes confere influências regionais de fatores climáticos diferentes, ocasionando volumes e intensidades pluviométricas distintas, o que reflete no resultado no índice de erosividade mensal e no fator R.Palavras-chave: estações pluviométricas; fator R; preenchimento de falhas; precipitação.